First report of the invasive Reticulitermes flavipes (Kollar, 1837) (Blattodea, Rhinotermitidae) in the Canary Islands. (2nd December 2018) - Hernández‐Teixidor, David; Suárez, Daniel; García, Javier; Mora, David
Abstract: Reticulitermes flavipes, one of the most harmful subterranean termite pests, is reported for the first time from Tenerife (Canary Islands, Spain). Cytochrome oxidase II was sequenced from five specimens in order to confirm the identification. To date, this invasive species has been detected in a limited area in the northeast of the island, affecting buildings, crops and native plant species. Another colony with the identical haplotype found in the southwest, 60 km away from the main population, indicates that this invasive insect may be more widespread over the island.